The challenge of consciousness with special reference to the exclusive disjunction - Antonites, Alex (HTS teologiese studies, 2015)
The theory of evolution makes sense of the emergence of consciousness. Reduction is not wrong as such, but must not be totalised. The fact that we are star stuff does not preclude the novelty of consciousness. Materialism is naturalism, but naturalism need not be materialism. Neural pathways are relevant but are not the total picture. The central thesis is about David Chalmers’s philosophy being based on an exclusive disjunction. An inclusive disjunction is, when explained, more appropriate. Functionalism is appropriate. Thomas Nagel’s philosophy on first person ontology can still be maintained. Quantum and complexity theories’ hypothesis on consciousness is more compatible with freedom of decision than classical theories.